2003
DOI: 10.1002/uog.114
|View full text |Cite
|
Sign up to set email alerts
|

New sonographic finding for the prenatal diagnosis of bladder exstrophy: a case report

Abstract: Bladder exstrophy is a very rare congenital malformation in which the anterior wall of the bladder is absent, and the posterior wall is exposed externally. Although sonographic findings of bladder exstrophy have been documented, we report a case presenting with a solid mass in the lower fetal abdomen with umbilical arteries running alongside the mass. The relationship between umbilical arteries and bladder exstrophy is a new sonographic finding which may be helpful in the prenatal diagnosis of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 7 publications
0
12
0
3
Order By: Relevance
“…Absence of a bladder became a crucial sign for confirming the diagnosis of cloacal exstrophy [4]. Lee et al [6] reported that, apart from the absence of a bladder, a solid mass in the lower fetal abdomen with umbilical arteries running alongside the mass is helpful for the diagnosis of cloacal exstrophy. Furthermore, Goldstein et al [7] reported a case in which the urachus resembled the normal bladder.…”
Section: Discussionmentioning
confidence: 98%
“…Absence of a bladder became a crucial sign for confirming the diagnosis of cloacal exstrophy [4]. Lee et al [6] reported that, apart from the absence of a bladder, a solid mass in the lower fetal abdomen with umbilical arteries running alongside the mass is helpful for the diagnosis of cloacal exstrophy. Furthermore, Goldstein et al [7] reported a case in which the urachus resembled the normal bladder.…”
Section: Discussionmentioning
confidence: 98%
“…Cette persistance anormale empêche la migration du tissu mésenchymateux entre l'ectoderme de l'abdomen et le cloaque entoblastique à la quatrième semaine de développement. Le défect plus ou moins important de recouvrement mésenchymateux alors provoqué dès la quatrième semaine de gestation peut alors être responsable d'un défaut de fusion de la paroi abdominale inférieure, de la symphyse pubienne, du tractus urinaire et des organes génitaux externes [1]. En cas d'extrophie, la perturbation de la mésenchymation entraîne une anomalie de situation, d'extension et du moment de la rupture de la membrane urogénitale.…”
Section: Rappels Embryologiquesunclassified
“…L'examen 2D doit permettre de rechercher des signes échographiques souvent associés [1,7,9] : une insertion basse du cordon ombilicale qui est inconstante ; une masse solide à la partie inférieure de la paroi abdominale correspondant à la plaque vésicale plus ou moins bourgeonnante, avec ou sans repli(s) ( Les extrophies vésicales sont souvent isolées, mais l'échographiste doit rechercher également les anomalies pouvant être associées aux coelosomies inférieures et entrant alors dans une association syndromique : l'omphalocèle, la fistule rectovésicale, l'agénésie du côlon terminal, l'imperforation anale, la malformation des organes génitaux externes ou encore une malformation des membres inférieurs [2]. D'autres anomalies sont également plus fréquentes et sont donc à rechercher : anomalies cardiovasculaires, rénales, squelettiques et du système nerveux central [2].…”
Section: Critères Diagnostiquesunclassified
See 1 more Smart Citation
“…The bladder is exposed into the amniotic cavity, due to the absence of its anterior wall; the posterior wall’s mucosa is in a more or less vegetative state and is directly followed by the adjacent cutaneous lay er [1]. …”
Section: Introductionmentioning
confidence: 99%